Exercise and free radical generation by contracting skeletal muscle - Jackson, Malcolm (Henry Stewart Talks, 2007)
Assessment of oxidative processes, ROS in skeletal muscle, ROS generation, Measurement of intracellular ROS, Potential actions of ROS in skeletal muscle, Effect of non-damaging contractile activity, HSP production in soleus muscles, Are adaptations of muscle to contractile activity mediated by oxidants?, ROS-induced effects on skeletal muscle, Antioxidant intervention studies, Muscle SOD and catalase activities, Muscle HSP60 content, Vitamin E supplementation
Archived at 2018/05/31